The Relationship between Transformational Leadership of School Administrators and Teachers’ Teamwork under the Office of the Private Education Commission, Chatuchak District, Bangkok - เจริญขำ เพ็ญรุ่ง; แก้วมงคล ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the level of transformational leadership among school administrators, 2) investigate the level of teachers’ teamwork, and 3) explore the relationship between transformational leadership and teachers’ teamwork under the Office of the Private Education Commission in Chatuchak District, Bangkok. The sample consisted of 239 teachers, with the sample size determined using Yamane’s formula. Stratified random sampling was employed based on school size, followed by proportional allocation and simple random sampling. The research instrument was a five-point Likert scale questionnaire, with an Index of Item–Objective Congruence (IOC) ranging from .80 to 1.00 and a reliability coefficient of .929, indicating high internal consistency. Data were analyzed using frequency, percentage, mean, standard deviation, and Pearson’s product–moment correlation coefficient. The findings indicated that: 1) the overall level of transformational leadership among school administrators was high (= 4.41, SD = 0.395). Among its dimensions, individualized consideration yielded the highest mean score (= 4.43, SD = 0.507), followed by inspirational motivation (= 4.41, SD = 0.429) and intellectual stimulation (= 4.40, SD = 0.439), whereas idealized influence demonstrated the lowest mean score (= 4.38, SD = 0.468), although it remained at a high level; 2) teachers’ teamwork was found to be at a high level overall (= 4.33, SD = 0.349). Collaboration showed the highest mean score (= 4.46, SD = 0.595), followed by communication (= 4.45, SD = 0.454) and coordination (= 4.26, SD = 0.428), while continuous improvement had the lowest mean score (= 4.23, SD = 0.519), though still within the high range; and 3) a strong positive correlation was found between transformational leadership and teachers’ teamwork (r = .806), which was statistically significant at the .01 level. These findings suggest that higher levels of transformational leadership are associated with more effective teamwork among teachers. significance at the .01 level, indicating that higher levels of transformational leadership are associated with higher levels of teamwork among teachers.